How Mathematical Reasoning Abilities can be improved? : A Study Case at Islamic Boarding School - Huda, Syamsul; Kharisma, Haya Nadirah; Qoma, Isti; Jermsittiparsert, Kittisak (Universitas Islam Negeri Raden Intan Lampung, 2020)
The development of mathematical reasoning ability of students affect the process of settlement of problems exiting in the process og learning matheatics. This study has the objective to determine the learning model that is effective between the Problem Based Learning models and the Learning Cycle 5E models. This study using quantitative study, data analysis techniques using T-test. The study results obtained it can be concluded that, mathematical reasoning ability of students has increased more effectively when the learning proces apply the Problem Based Learning models.